15q13.3 duplication in two patients with childhood‐onset schizophrenia. Issue 6 (10th March 2016) - Zhou, Dale; Gochman, Peter; Broadnax, Diane D.; Rapoport, Judith L.; Ahn, Kwangmi
Abstract : We report two cases of paternally inherited 15q13.3 duplications in carriers diagnosed with childhood‐onset schizophrenia (COS), a rare neurodevelopmental disorder of proposed polygenic origin with onset in children before age 13. This study documents that the 15q13.3 deletion and duplication exhibit pathogenicity for COS, with both copy number variants (CNVs) sharing a disrupted CHRNA7 gene. CHRNA7 encodes the neuronal alpha7 nicotinic acetylcholine receptor (α7nAChR) and is a candidate gene that has been suggested as a pathophysiological process mediating adult‐onset schizophrenia (AOS) and other neurodevelopmental disorders. These results support the incomplete penetrance and variable expressivity of this CNV and represent the first report of 15q13.3 duplication carriers exhibiting COS. Published 2016. This article is a U.S. Government work and is in the public domain in the USA. American Journal of Medical Genetics Part B: Neuropsychiatric Genetics published by Wiley Periodicals, Inc.